Factors Influencing Learners' Motivation in Mobile-Assisted Language Learning: A Case Study on Four Chinese EFL Learners - Ke Yang (Cranmore Publishing, 2020)
As mobile-assisted language learning (MALL) has become increasingly popular among learners of English, their motivation in using mobile technologies to learn the language has attracted the attention of researchers. This study investigates possible factors that may influence learners' motivation in MALL in natural learning environments. A case study was conducted involving four Chinese adult EFL learners who used a mobile application named MintReading for eight weeks. Weekly learning journals and semi-structured interviews were conducted to collect in-depth data from each participant. The results indicated that the following affected learners' motivation as they were learning: (1) interesting and useful reading content; (2) language difficulties; (3) affordance of mobile technologies; (4) motivational design of the application. On the other hand, their interaction with an online community, that of the social media app WeChat, failed to contribute to their learning motivation. Discussions of the research findings are based on self-determination theory, and implications and limitations of this study are also addressed.